Coordinated actions of NLR-assembled and glutamate receptor–like calcium channels in plant effector-triggered immunity - Junli Wang; Xinhua Sun; Fei Xiong; Dmitry Lapin; Tak Lee; Sergio Martin-Ramirez; Anna Prakken; Qiaochu Shen; Jaqueline Bautor; Takaki Maekawa; Jane E. Parker (Proceedings of the National Academy of Sciences, 2025)
The plant immune system utilizes nucleotide-binding/leucine-rich repeat (NLR) proteins to detect pathogen virulence factors (effectors) inside host cells and transduce recognition to rapid defense. In dicotyledenous plants, pathogen activated Toll-like/interleukin-1 receptor-containing NLRs (TNLs) establish a signaling network of enhanced susceptibility 1 (EDS1)-family dimers with RPW8-type coiled-coil (CC R ) domain NLRs (RNLs) to stimulate transcriptional reprogramming leading to host cell death and pathogen restriction. Evidence suggests that TNL- and EDS1-activated RNLs function as oligomeric Ca 2+ permeable ion channels at the plasma membrane. However, the downstream processes for immunity execution are poorly understood. Here, we studied pathogen effector-triggered immunity conferred by Nicotiana benthamiana TNL (Roq1) which signals almost exclusively through the EDS1-senescence associated gene101 (SAG101)-N required gene 1 (NRG1) RNL module. We identify a pair of glutamate receptor–like Ca 2+ ion channels (GLR2.9a and GLR2.9b) which, unlike most other pathogen-induced GLRs, are highly up-regulated by the EDS1-SAG101-NRG1 module in the TNL immune response. We show that oligomeric NRG1 Ca 2+ channel activity is necessary for GLR2.9a and GLR2.9b induced expression. Consequently, GLR2.9a and GLR2.9b proteins contribute to NRG1 -dependent Ca 2+ accumulation in host cells, and to pathogen resistance and host cell death. We establish that GLR2.9a localizes mainly to the plasma membrane/cytoplasm whereas GLR2.9b accumulates preferentially at the nuclear envelope. The data show that transcriptionally up-regulated canonical Ca 2+ ion channels GLR2.9a and GLR2.9b are a functional output of the EDS1-SAG101-NRG1 module for TNL-triggered immunity.